Video Tutorial English Kuy untuk Pembelajaran Bahasa Inggris Pariwisata - Putu Dian Danayanti Degeng; Irene Nany Kusumawardani; Galuh Nurul Indah Asri; Eleazar Evan Moeljono (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2021)
This research was conducted to develop a video tutorial as a medium of English learning activity in the thematic village of Kajoetangan Malang. English Kuy was developed using an instructional media development model from Lee and Owens. Based on the results of experts validation, it can be concluded that this video tutorial is theoretically suitable and can be used as a medium of learning English for the basic/beginner level. The English Kuy video tutorials can be used by tourism workers in Malang, especially food vendors, food stall owners, or the general public who are interested in learning basic or beginner-level English about tourism and hospitality.